Bioprospeksi: Eksplorasi Senyawa Aktif Penurun Penderita Stroke dari Organisme Laut - Putri, Radwa Fathin H; Yufani, Rofika An; Saniyawati, Fang You Dwi Ayu Shalu; Safitri, Anna (Penerbit Brainy Bee, 2025)
Stroke is a deadly disease in Indonesia. Meanwhile, marine organisms can contribute to providing active compounds for anti-stroke. The purpose of this review is to provide an overview of stroke sufferers in Indonesia and to identify potential active compounds from marine organisms that can treat or prevent stroke. The writing method was carried out by tracing the literature related to stroke and organisms that produce anti-stroke active compounds through Google Scholar. After collecting data from various literature, the next step was to process the data using simple statistics. Marine organisms that potentially contain anti-stroke active compounds are sea cucumbers (DHA, Docosahexaenoic acid), sea urchins (flavonoids), starfish (flavonoids), and jellyfish (amino acids), while marine organism biomarkers are biological responses of all living things in the sea to pollution and environmental pressures. This review is expected to be the beginning of the development of bioprospecting based on omics: metabarcoding and metagenomics, transcriptomics, proteomics, glycomics, lipidomics, and metabolomics.